Paclitaxel in the Treatment of Carcinosarcoma of the Uterus: A Gynecologic Oncology Group Study - Curtin, John P.; Blessing, John A.; Soper, John T.; DeGeest, Koen (Gynecologic oncology, 2001)
Objective. The goal of this study was to estimate the clinical activity of paclitaxel in patients with persistent or recurrent carcinosarcoma of the uterus who have failed other treatments. Methods. The Gynecologic Oncology Group (GOG) conducted a phase II study of paclitaxel 170 mg/m2 (135 mg/m2 in those with prior irradiation) intravenously every 3 weeks in patients with histologic confirmation of carcinoma and measurable disease who had failed appropriate local therapy. Results. A total of 53 patients were entered into the study between September 1994 and January 1997; 44 patients were evaluable for response. The median age of the patients treated was 65 years (range: 38–79). Twenty-six patients had heterologous mixed mesodermal tumors (MMTs) and 18 patients had homologous tumors. A median of three courses were administered (range: 1–18). Fifteen patients had previous radiation therapy and 33 patients had failed prior chemotherapy. Eight patients (18.2%) had a response to paclitaxel: four patients had a complete response and four had a partial response. Neutropenia was the most common toxic effect. Conclusions. Paclitaxel had moderate activity in patients with carcinosarcoma of the uterus. The GOG is currently studying the combination of paclitaxel and ifosfamide versus ifosfamide alone for patients with advanced or recurrent carcinosarcoma of the uterus.